PhD in Archaeology - Croatian Perspective - Potrebica, Hrvoje (Array, 2011)
This paper will give brief overview of current state of PhD in Archaeology programmes in Croatia and emphasize the most important problems and issues related to former as well as current “transitional” curricula. The primary problem of PhD studies is their content – or what is PhD supposed to be (genuine scientific research and original contribution, or qualification work which proves ability of the candidate to pursue such goals in his/hers future scientific career)? Another question is form of such studies, especially in context of Bologna Process. The main issue of that discussion should be achieving basic complementarity on European level, which is necessary for mobility as pivotal concept of Bologna Process in general.